Response of adult dragonflies to artificial prey of different size and colour. - Tammy M Duong; Ann B Gomez; Thomas N Sherratt (PLoS ONE)
Aposematism is an evolved, cross-species association between a preys' unprofitability and the presence of conspicuous signals. Avian predators have been widely employed to understand the evolution of these warning signals However, insect predators are abundant, diverse, and highly visual foragers that have been shown to be capable of learned aversion. Therefore, it is likely that their behaviour also shapes the nature of anti-predator traits. In this study, we evaluated the rates of attack of a community (13 species) of mature adult dragonflies (Odonata) on artificial prey of varying size (2.5-31 mm lengthwise) and colour pattern (black, black/yellow striped). The relative attack rates of dragonflies on prey increased as prey size decreased, but there was no evidence that the attack rates by dragonflies were affected by prey colour pattern and no evidence for an interaction between colour pattern and size. To investigate prey selection by specific predator species under field conditions, we compared the time to attack distributions of black-painted prey presented to two common dragonflies: Leucorrhinia intacta and the larger, Libellula pulchella. We found that the two dragonfly species, as well as the two sexes, had different foraging responses. L. pulchella was more likely to attack larger prey, and females of both species more likely to attack prey than males. Collectively, our results indicate that dragonflies are highly size selective. However, while the nature of this selectivity varies among dragonfly species, there is little evidence that classic black/yellow warning signals deter attack by these aerial invertebrate predators.